The Course of Tuberculosis in Elderly Patients with Comorbid Background (Eurasian Medical Research Periodical, 2023)
Pulmonary tuberculosis often develops against the background of diseases that lead to dysfunction of organs and systems, and in a joint course, they have a mutually aggravating interaction. This complicates the timely diagnosis of tuberculosis, and in the treatment entails forced polypharmacy, the development of drug complications and failures in treatment.